Age Discrimination as a Threat to the Anthropological Absolute of Human Being (Using the Pandemic Crisis as an Example) - Blikhar, V. S.; Hren, N. M. (Anthropological Measurements of Philosophical Research, 2021)
Purpose. The purpose of this paper is to investigate the anthropological and socio-philosophical dimensions of human existence of the older age group given the challenges of pandemic threats caused by COVID-19. To this end, it is planned to solve a number of tasks, among which one should distinguish the following: 1) to investigate the manifestations of age discrimination in the context of the social and labor areas of human existence; 2) to focus on the asymmetry of the behavior of society and the state relative to persons of the older age group in the field of healthcare in the context of a pandemic crisis; 3) to represent the anthropological features of changes in the socialization and activity of older people under the current conditions of globalization-pandemic challenges. Theoretical basis. Despite such a broad representation of the age-related issue in public relations, there are still no practical guarantees that would apply to discriminatory aspects of older age groups in various areas of their manifestation. The synergistic evolution of social reality requires substantive analysis of the issue under the current conditions for the transformation of social life, which is affected by globalization crises caused by the pandemic threats of COVID-19. Originality. The stereotypical assumptions underlying legal policy and established social relations are based solely on the application of chronological age. The novelty is in justifying an individual approach to the elderly through the personification of the personal characteristics of a person. The study of anthropological and socio-philosophical dimensions of the existence of a person of the older age group in the face of the challenges of pandemic threats caused by COVID-19 has made it possible to analyze the destructive nature of age discrimination in the context of the social and labor areas of human existence. As well as focus on the asymmetry of the behavior of society and the state in relation to these persons in the field of health care, and emphasize the anthropological features of changes in the socialization and human activity under the current conditions of globalization-pandemic challenges. Conclusions. External threats to human existence call for special attention to the implementation and protection of human rights, freedoms, individual freedoms, and identity. Pandemic threats have transformed all dimensions of human existence, especially for those groups of society that are less socially protected. The pandemic crisis has created additional grounds for discrimination against older people in various areas of human existence. Equalization of persons by age without personifying the personal characteristics of an individual is discrimination on an age basis, which violates the principles of democracy and humanism in the society, leads to stigmatization of the person, is the cause of the anthropological crisis of a person.